SAFE: an eHealth intervention for women experiencing intimate partner violence - study protocol for a randomized controlled trial, process evaluation and open feasibility study - N. E. van Gelder; K. A. W. L. van Rosmalen-Nooijens; S. A Ligthart; J. B. Prins; S. Oertelt-Prigione; A. L. M. Lagro-Janssen (BMC, 2020)
Abstract Background Intimate partner violence (IPV) affects almost one in three women worldwide. However, disclosing violence or seeking help is difficult for affected women. eHealth may represent an effective alternative to the standard support offers, which often require face-to-face interaction, because of easy accessibility and possibility of anonymous usage. In the Netherlands we are developing SAFE, an eHealth intervention for female victims of IPV, which will be evaluated in a randomized controlled trial and a process evaluation, followed by an open feasibility study to assess real-world user data. Methods/design The randomized controlled trial is a two-arm parallel design comparing an intervention arm and a control group. The groups both have access to eHealth but differ in the offer of interactive features compared to static information. Both groups complete questionnaires at three or four time points (baseline, three months, six months, 12 months) with self-efficacy at 6 months as the primary outcome, measured with the General Self-Efficacy (GSE) scale. The process evaluation consists of quantitative data (from the website and from web evaluation questionnaires) and qualitative data (from interviews) on how the website was used and the users' experiences. Discussion eHealth has the potential to reach a large number of women who experience IPV. The internet-based design can lower access barriers and encourage help-seeking behavior ultimately reducing the lag time between subjective awareness and protective action. Trial registration Trial registered on 15 August 2017 at the Netherlands Trial Register NL7108 (NTR7313).